Surgical Procedures for Neuroendocrine Neoplasms of the Appendix: A Consensus Guideline Review - Paulina Vladova; Sergey Iliev; Savelina Popovska (Journal of Biomedical & Clinical Research)
According to the consensus and the recommendations of the European Neuroendocrine Tumor Society (ENETS), the frequency of appendicular neuroendocrine tumors (NETs) is 0.15-0.6/100 000 a year. They are found a little more often in women aged between 40 and 50. Neuroendocrine neoplasms of the appendix are about 30 to 80% of all appendicular tumors. Their evolution is usually asymptomatic. They are diagnosed accidentally during a conventional or laparoscopic appendectomy. In the past, the surgical approach used to depend on the localization of the tumor. Currently, its localization is not a significant factor in the choice of a surgical approach. Our purpose wass to present the consensus guideline and the recommendations of ENETS 2017 for surgical procedures in neuroendocrine neoplasms of the appendix and analyze the difference in the survival rate in different surgical interventions. The literature overview includes studies on surgical treatment of neuroendocrine neoplasms of the appendix and takes into consideration the last consensus guideline of ENETS 2017 on the topic. ENETS recommends a simple appendectomy in well- differentiated appendix tumors smaller than 2 cm, regardless of their localization. Right hemicolectomy is performed for in tumors sized between 1 cm and 2 cm with positive resection lines, with deep mesoappendiceal invasion, high proliferation activity (G2) and vascular invasion. For tumors over larger than 2 cm – right hemicolectomy is recommended. Although current studies have pointed out no significant differences in survival rates between appendectomy for neuroendocrine neoplasms of the appendix and right hemicolectomy, ENETS 2017 suggests that the latest consensus guidelines should be followed.